2019
DOI: 10.1002/smll.201901848
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nitrogen‐Doped Carbon for Zinc–Bromine Flow Battery

Abstract: The zinc–bromine flow battery (ZBFB) is one of the most promising technologies for large‐scale energy storage. Here, nitrogen‐doped carbon is synthesized and investigated as the positive electrode material in ZBFBs. The synthesis includes the carbonization of the glucose precursor and nitrogen doping by etching in ammonia gas. Physicochemical characterizations reveal that the resultant carbon exhibits high electronic conductivity, large specific surface area, and abundant heteroatom‐containing functional group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…They report that the total amount of nitrogen decreases with increasing temperature, and that the proportion of graphitic nitrogen increases, while the proportion of pyridinic nitrogen decreases. A zinc bromine flow cell employing carbon spheres doped with nitrogen at 1000 °C achieved an energy efficiency of 82.5 % at 80 mA cm −2 , compared to 76.0 % with unmodified carbon spheres [93] …”
Section: Carbon‐based Bromine Electrodes In Rfb Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…They report that the total amount of nitrogen decreases with increasing temperature, and that the proportion of graphitic nitrogen increases, while the proportion of pyridinic nitrogen decreases. A zinc bromine flow cell employing carbon spheres doped with nitrogen at 1000 °C achieved an energy efficiency of 82.5 % at 80 mA cm −2 , compared to 76.0 % with unmodified carbon spheres [93] …”
Section: Carbon‐based Bromine Electrodes In Rfb Systemsmentioning
confidence: 99%
“…Chemical doping with hetero‐atoms can modulate the electronic properties of carbon material. Nitrogen doping can help achieve appropriate electron modulation for electrocatalytic process owing to its higher electronegativity [91–93] . Xiang et al .…”
Section: Carbon‐based Bromine Electrodes In Rfb Systemsmentioning
confidence: 99%
“…Studies reported in the field of energy storage consider carbon spheres as a promising material/catalyst because of their high surface area, chemical stability, and cost-effectiveness [20][21][22][23]. It has explained in the literature that, N-doped carbon materials facilitate the formation of defects sites on the electrode surface which helps in the electrolyte absorption and hence increases the wettability of the electrode [17,18,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However very few reports available on the single-step hydrothermal synthesis of nitrogendoped carbon spheres using dextrose and ammonia as the precursors [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the redox flow batteries own advantages of high efficiency, long cycle life, and power/energy independent sizing . The zinc‐bromine redox flow battery (ZBB) is a promising candidate for its relatively high energy density (65–75 Wh/kg) and high cell voltage (1.82 V) compared with other similar systems . On the other side, the energy density is yet inferior to the rechargeable batteries based on zinc (Zn) metal anode, such as Ag−Zn (150 Wh/kg) and Zn−Ni .…”
Section: Introductionmentioning
confidence: 99%